Soil Microbiome Inoculation for Resilient and Multifunctional New Forests in Post‐Agricultural Landscapes - Sofia I. F. Gomes; Per Gundersen; T. Martijn Bezemer; Davide Barsotti; Ludovica D'Imperio; Konstantinos Georgopoulos; Mathias Just Justesen; Karelle Rheault; Yamina M. Rosas; Inger Kappel Schmidt; Leho Tedersoo; Lars Vesterdal; et al. (Global Change Biology, 2025)
Afforestation is increasingly recognized as a critical strategy to restore ecosystems and enhance biodiversity on post‐agricultural landscapes. However, agricultural legacies, such as altered soil structure, nutrient imbalances, and depleted microbial diversity, can slow down forest establishment or cause ecosystems to deviate from expected successional trajectories. In this opinion paper, we explore the potential of soil inoculations as a tool to overcome these challenges by introducing beneficial microbial communities that can accelerate ecosystem recovery and forest development. Restoring soil biodiversity is a crucial aspect of this process that drives broader ecosystem functionality and resilience. We highlight the need to carefully consider the type and timing of inoculations and to ensure compatibility between the inoculum and recipient site characteristics to optimize the establishment of introduced species. While tree productivity is often a central focus of afforestation efforts, the restoration of soil biodiversity, which will also contribute to increased ecosystem‐level functions, should also be a priority for long‐term forest resilience. Agricultural legacies add complexities to the restoration process, creating unique challenges that need to be addressed in restoration planning. Thus, successful inoculation strategies require a thorough understanding of both donor and recipient site characteristics, also in relation to potential mismatches related to soil physiochemical properties to avoid unintended consequences such as the non‐establishment of introduced species. Additionally, we call for the re‐evaluation of afforestation targets and the development of standardized monitoring protocols that track the success of inoculation efforts, particularly regarding soil health, microbial community establishment, and biodiversity recovery. By integrating inoculation practices within a broader restoration framework, we can enhance the resilience, biodiversity, and ecosystem functionality of newly afforested landscapes. Ultimately, this approach may play a critical role in ensuring the success of large‐scale afforestation projects.

Arctic and Atlantic Waters in the Norwegian Basin, Between Year Variability and Potential Ecosystem Implications - Øystein Skagseth; Cecilie Broms; Kjell Gundersen; Hjálmar Hátún; Inga Kristiansen; Karin Margretha H. Larsen; Kjell Arne Mork; Hildur Petursdottir; Henrik Søiland (Frontiers in Marine Science, 2022)
The ocean climate of the southern Norwegian Sea - the Norwegian Basin - is largely set by the relative amount of Atlantic Water in the eastern and Arctic Water in the western region. Here we utilized hydrographic data from repeated sections, together with annually gridded survey data of the upper 1000 m, to resolve the main hydrographic changes over the period 1995-2019. Based on integrated heat -and freshwater content, we divide into three periods. The first period 1995-2005, denoted Arctic, is characterized by relative fresh and cold Atlantic Water overlaying Arctic Intermediate Water that basically covers the whole Norwegian Basin. Differently, the conditions during the period 2006-2016, denoted Atlantic, are warmer and more saline, and the extent and thickness of Arctic Intermediate Water is greatly reduced. During the most recent period denoted Fresh, 2017-2019, there has been a major freshening of the Atlantic waters, the layer of Arctic Intermediate Water has not recovered, but instead a layer of warmer but relative fresh Arctic Water has expanded. We find that increased abundance of the Arctic zooplankton Calanus hyperboreus in the southern and eastern Norwegian Basin coincides with increased extent of Arctic Water. We also note that the overall mesozooplankton biomass in the Norwegian Basin is significantly higher during periods of relative high amount of Arctic Water. Furthermore, we show that both nitrate and silicate winter (pre-bloom) concentrations are significantly higher in the Arctic Water compared to Atlantic Water, and that there is a reduction in nutrients from the Arctic period compared subsequent Atlantic and Fresh periods. Since these nutrients can be interpreted as the potential for new production, changes in the influx of western Arctic waters are expected to have a bottom-up effect on the Norwegian Sea. Hence, this study indicates that the amount of Arctic waters and their concentration of nutrients and zooplankton are more important for the Norwegian Basin ecosystem functioning rather than the temperature of the Atlantic waters.

CropPol : A dynamic, open and global database on crop pollination - Alfonso Allen‐Perkins; Ainhoa Magrach; Matteo Dainese; Lucas A. Garibaldi; David Kleijn; Romina Rader; James R. Reilly; Rachael Winfree; Ola Lundin; Carley M. McGrady; Claire Brittain; David J. Biddinger; et al. (Ecology, 2022)
Seventy five percent of the world's food crops benefit from insect pollination. Hence, there has been increased interest in how global change drivers impact this critical ecosystem service. Because standardized data on crop pollination are rarely available, we are limited in our capacity to understand the variation in pollination benefits to crop yield, as well as to anticipate changes in this service, develop predictions, and inform management actions. Here, we present CropPol, a dynamic, open, and global database on crop pollination. It contains measurements recorded from 202 crop studies, covering 3,394 field observations, 2,552 yield measurements (i.e., berry mass, number of fruits, and fruit density [kg/ha], among others), and 47,752 insect records from 48 commercial crops distributed around the globe. CropPol comprises 32 of the 87 leading global crops and commodities that are pollinator dependent. Malus domestica is the most represented crop (32 studies), followed by Brassica napus (22 studies), Vaccinium corymbosum (13 studies), and Citrullus lanatus (12 studies). The most abundant pollinator guilds recorded are honey bees (34.22% counts), bumblebees (19.19%), flies other than Syrphidae and Bombyliidae (13.18%), other wild bees (13.13%), beetles (10.97%), Syrphidae (4.87%), and Bombyliidae (0.05%). Locations comprise 34 countries distributed among Europe (76 studies), North America (60), Latin America and the Caribbean (29), Asia (20), Oceania (10), and Africa (7). Sampling spans three decades and is concentrated on 2001–2005 (21 studies), 2006–2010 (40), 2011–2015 (88), and 2016–2020 (50). This is the most comprehensive open global data set on measurements of crop flower visitors, crop pollinators and pollination to date, and we encourage researchers to add more datasets to this database in the future. This data set is released for non‐commercial use only. Credits should be given to this paper (i.e., proper citation), and the products generated with this database should be shared under the same license terms (CC BY‐NC‐SA).

Organochlorine and Metal Contaminants in the Blood Plasma of Green Sturgeon Caught in Washington Coastal Estuaries - Julie A. Layshock; Molly A. H. Webb; Olaf P. Langness; John Carlos Garza; Laura B. Heironimus; Deke Gundersen (Archives of Environmental Contamination and Toxicology, 2022)

Correction to: Vertical Redistribution of Soil Organic Carbon Pools After Twenty Years of Nitrogen Addition in Two Temperate Coniferous Forests - Stefan J. Forstner; Viktoria Wechselberger; Stefanie Müller; Katharina M. Keiblinger; Eugenio Díaz-Pinés; Wolfgang Wanek; Patrick Schleppi; Frank Hagedorn; Per Gundersen; Michael Tatzber; Martin H. Gerzabek; Sophie Zechmeister-Boltenstern (Ecosystems, 2019)

Vertical Redistribution of Soil Organic Carbon Pools After Twenty Years of Nitrogen Addition in Two Temperate Coniferous Forests - Stefan J. Forstner; Viktoria Wechselberger; Stefanie Müller; Katharina M. Keibinger; Eugenio Díaz-Pinés; Wolfgang Wanek; Patrick Scheppi; Frank Hagedorn; Per Gundersen; Michael Tatzber; Martin H. Gerzabek; Sophie Zechmeister-Boltenstern (Ecosystems, 2019)

Tissue Contaminant Burdens in San Francisco Estuary White Sturgeon (Acipenser transmontanus): Implications for Population Recovery - Deke T. Gundersen; Steven C. Zeug; Robert B. Bringolf; Joseph Merz; Zachary Jackson; Molly A. H. Webb (Archives of Environmental Contamination and Toxicology, 2017)

Status, trends and drivers of kelp forests in Europe: an expert assessment - R. M. Araújo; J. Assis; R. Aguillar; L. Airoldi; I. Bárbara; I. Bartsch; T. Bekkby; H. Christie; D. Davoult; S. Derrien-Courtel; C. Fernandez; S. Fredriksen; et al. (Biodiversity and Conservation, 2016)

Genetic diversity of the NE Atlantic sea urchin Strongylocentrotus droebachiensis unveils chaotic genetic patchiness possibly linked to local selective pressure - K. M. Norderhaug; M. B. Anglès d’Auriac; C. W. Fagerli; H. Gundersen; H. Christie; K. Dahl; A. Hobæk (Marine Biology, 2016)

Soil carbon stock change following afforestation in Northern Europe: a meta‐analysis - T. G. Bárcena; L. P. Kiær; L. Vesterdal; H. M. Stefánsdóttir; P. Gundersen; B. D. Sigurdsson (Global Change Biology, 2014)
Northern Europe supports large soil organic carbon ( SOC ) pools and has been subjected to high frequency of land‐use changes during the past decades. However, this region has not been well represented in previous large‐scale syntheses of land‐use change effects on SOC , especially regarding effects of afforestation. Therefore, we conducted a meta‐analysis of SOC stock change following afforestation in Northern Europe. Response ratios were calculated for forest floors and mineral soils (0–10 cm and 0–20/30 cm layers) based on paired control (former land use) and afforested plots. We analyzed the influence of forest age, former land‐use, forest type, and soil textural class. Three major improvements were incorporated in the meta‐analysis: analysis of major interaction groups, evaluation of the influence of nonindependence between samples according to study design, and mass correction. Former land use was a major factor contributing to changes in SOC after afforestation. In former croplands, SOC change differed between soil layers and was significantly positive (20%) in the 0–10 cm layer. Afforestation of former grasslands had a small negative (nonsignificant) effect indicating limited SOC change following this land‐use change within the region. Forest floors enhanced the positive effects of afforestation on SOC , especially with conifers. Meta‐estimates calculated for the periods 30 years since afforestation revealed a shift from initial loss to later gain of SOC . The interaction group analysis indicated that meta‐estimates in former land‐use, forest type, and soil textural class alone were either offset or enhanced when confounding effects among variable classes were considered. Furthermore, effect sizes were slightly overestimated if sample dependence was not accounted for and if no mass correction was performed. We conclude that significant SOC sequestration in Northern Europe occurs after afforestation of croplands and not grasslands, and changes are small within a 30‐year perspective.

Sinks for nitrogen inputs in terrestrial ecosystems: a meta‐analysis of 15 N tracer field studies - P. H. Templer; M. C. Mack; F. S. Chapin III; L. M. Christenson; J. E. Compton; H. D. Crook; W. S. Currie; C. J. Curtis; D. B. Dail; C. M. D'Antonio; B. A. Emmett; H. E. Epstein; et al. (Ecology, 2012)
Effects of anthropogenic nitrogen (N) deposition and the ability of terrestrial ecosystems to store carbon (C) depend in part on the amount of N retained in the system and its partitioning among plant and soil pools. We conducted a meta‐analysis of studies at 48 sites across four continents that used enriched 15 N isotope tracers in order to synthesize information about total ecosystem N retention (i.e., total ecosystem 15 N recovery in plant and soil pools) across natural systems and N partitioning among ecosystem pools. The greatest recoveries of ecosystem 15 N tracer occurred in shrublands (mean, 89.5%) and wetlands (84.8%) followed by forests (74.9%) and grasslands (51.8%). In the short term ( 15 N tracer application), total ecosystem 15 N recovery was negatively correlated with fine‐root and soil 15 N natural abundance, and organic soil C and N concentration but was positively correlated with mean annual temperature and mineral soil C:N. In the longer term (3–18 months after 15 N tracer application), total ecosystem 15 N retention was negatively correlated with foliar natural‐abundance 15 N but was positively correlated with mineral soil C and N concentration and C : N, showing that plant and soil natural‐abundance 15 N and soil C:N are good indicators of total ecosystem N retention. Foliar N concentration was not significantly related to ecosystem 15 N tracer recovery, suggesting that plant N status is not a good predictor of total ecosystem N retention. Because the largest ecosystem sinks for 15 N tracer were below ground in forests, shrublands, and grasslands, we conclude that growth enhancement and potential for increased C storage in aboveground biomass from atmospheric N deposition is likely to be modest in these ecosystems. Total ecosystem 15 N recovery decreased with N fertilization, with an apparent threshold fertilization rate of 46 kg N·ha −1 ·yr −1 above which most ecosystems showed net losses of applied 15 N tracer in response to N fertilizer addition.

Using Blood Plasma for Monitoring Organochlorine Contaminants in Juvenile White Sturgeon, Acipenser transmontanus, from the Lower Columbia River - D. T. Gundersen; M. A. H. Webb; A. K. Fink; L. R. Kushner; G. W. Feist; M. S. Fitzpatrick; E. P. Foster; C. B. Schreck (Bulletin of Environmental Contamination and Toxicology, 2008)

Assessment ofsolatium hougasii in Washington and Mexico as a source of resistance to late blight - D. A. Inglis; C. R. Brown; B. G. Gundersen; L. D. Porter; J. S. Miller; D. A. Johnson; H. Lozoya-Saldaña; K. G. Haynes (American Journal of Potato Research, 2007)

Mercury Concentrations in Gonad, Liver, and Muscle of White Sturgeon Acipenser transmontanus in the Lower Columbia River - M. A. H. Webb; G. W. Feist; M. S. Fitzpatrick; E. P. Foster; C. B. Schreck; M. Plumlee; C. Wong; D. T. Gundersen (Archives of Environmental Contamination and Toxicology, 2006)

Modelling the advection and diffusion of eggs and larvae of Greenland halibut ( Reinhardtius hippoglossoides ) in the north‐east Arctic - Bjørn Ådlandsvik; Agnes C. Gundersen; Kjell H. Nedreaas; Anne Stene; Ole T. Albert (Fisheries Oceanography, 2004)
Since the late 1980s there has been considerable uncertainty in recruitment levels of the north‐east Arctic stock of Greenland halibut ( Reinhardtius hippoglossoides ). The abundance of several year classes, originally considered very low at 0–3 yr age, appeared higher than expected at the age of 6+. This may be due to poor targeting of recruitment surveys of the younger year classes. The present work considers the transport and dispersion of eggs and larvae of Greenland halibut by numerical modelling in order to predict the locations of the initial recruitment grounds. Current fields from a 3D baroclinic hydrodynamic model are fed into a Lagrangian particle‐tracking model developed for the Barents Sea area. The particles are released into the current at the spawning field along the shelf slope from Lofoten to Bear Island (69–75°N). Vertically, the particles can follow a predefined depth‐by‐age curve or be kept at a fixed depth. This model system is used for different years to examine changes in the drift pattern. The results indicate that spawning location, transport depth and inflowing activity to the Barents Sea are important factors influencing the distribution of juveniles.

Elemental C, N, and P cell content of individual bacteria collected at the Bermuda Atlantic Time‐series Study (BATS) site - Kjell Gundersen; Mikal Heldal; Svein Norland; Duncan A. Purdie; Anthony H. Knap (Limnology and Oceanography, 2002)
Accurate assessments of the true elemental cellular content of carbon (C), nitrogen (N), and phosphorus (P) in bacteria have been a major difficulty in microbial research for some time. This study is the first to present single‐cell elemental C, N, and P measurements on natural populations of bacteria from the Sargasso Sea using a transmission electron microscope (TEM) equipped with an X‐ray detector unit. Elemental cell content showed a best fit as a power function of the cell size, and smaller bacteria had significantly more elemental C, N, and P per cell volume than the larger ones (scaling factor a −3 ) was higher than any other estimates reported from coastal and brackish water systems. Total amount of bacterial C calculated from abundance estimates requires an average conversion factor, and the choice of a representative bacterial cell volume is therefore critical. We were able to demonstrate that the outcome of biomass assessments is highly dependant on the choice of cell‐specific conversion factors. By applying cell volumes previously reported from the BATS site, the average 0–250 m depth integration of bacterial C between 1991 and 1996 ranged between 1.7 and 2.5 times less than other recent biomass estimates for these waters.

s of papers presented at the 81st annual meeting of The Potato Association of America Charlottetown, P.E.I., Canada August 3 – 7, 1997 - S. T. Ali-Khan; C. Hetner; L. Ladislav; V. Currie; Walter J. Arsenault; A. Naseer Aziz; Janet E. A. Seabrook; George C. C. Tai; J. B. Bamberg; Alfonso H. del Rio; Max Martin; J. B. Bamberg; et al. (American Journal of Potato Research, 1997)